Answer :

Let’s use algebra. starting with x,y, the square of the difference is is = + - 2

the square of the sum is

= + + 2

what if we subtract the square of the difference from the square of the sum.

- = (+ + 2 - (+ - 2)

- =

writing this in reverse

= -

for example, 24= 4

= here x=6 and y=1

= -

= -

= 7^{2} – 5^{2}

similarly 24 can also be written as

24 = 432

= here x=3 and y=2

= -

= -

= 5^{2} – 1^{2}

so 24 =7^{2} – 5^{2}= 5^{2} – 1^{2}

other multiple of 8,

32 = 9^{2} – 7^{2} = 6^{2} – 2^{2}

32 = 481

= here x=8 and y=1

= -

= -

= 9^{2} – 7^{2}

similarly 32 can also be written as

32 = 442

= here x=4 and y=2

= -

= -

32 = 9^{2} – 7^{2} = 6^{2} – 2^{2}

Rate this question :

<span lang="EN-USKerala Board Mathematics Part I

<span lang="EN-USKerala Board Mathematics Part I

<span lang="EN-USKerala Board Mathematics Part I

<span lang="EN-USKerala Board Mathematics Part I

<span lang="EN-USKerala Board Mathematics Part I

<span lang="EN-USKerala Board Mathematics Part I

<span lang="EN-USKerala Board Mathematics Part I

<span lang="EN-USKerala Board Mathematics Part I

<span lang="EN-USKerala Board Mathematics Part I

<span lang="EN-USKerala Board Mathematics Part I